(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Urea can be supplied to plants through the foliage, facilitating optimal N management, which minimizes N losses to the environment. The efficiency of N assimilation through foliage depends upon several factors including N levels and varieties or genotypes. No information is available on the effect of the foliar application of urea on stevia (Stevia rebaudiana, Bertoni). The objective of the study was to evaluate the effect of foliar application of prilled urea applied in different concentrations on the growth, yield components, leaf biomass yield, N content and its uptake by stevia. Seven levels of urea viz. 0.0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3g 2L-1 were sprayed 10 days after planting (DAP) in acid and non-calcareous soils at an interval of one week up to 60 DAP. Foliar urea application significantly increased plant height, branch and leaf number, leaf area, fresh and dry leaf weight, leaf N content and uptake by stevia. Most of the parameters were increased with the advancement of growth period from 30 to 60 DAP. The foliar spray of 2.0g urea solution was found to be most effective for enhancing the growth, leaf yield and yield attributes of stevia. The yield increase was 478% in acid soil and 485% in non-calcareous soil over control. Further increase in the concentrations of urea spray (2.5 and 3.0g) was not found to be useful as it declined the leaf yield by 135% in acid and 175% in non-calcareous soil probably due to its toxicity. N content in stevia leaves was significantly increased with the increased levels of urea up to 3.0g in both soils. Conversely, the trend of N uptake did not follow the trend of N contents of stevia leaves. N uptake as expected increased as foliar application of urea increased up to 2.0g and then decreased with further addition. The results suggest that farmers can be advised to apply prilled urea as foliar spray @ 1g L-1 for higher leaf biomass yield and N uptake by stevia either in acid or non-calcareous soils under the agro-climatic conditions of Bangladesh Agricultural University, Mymensingh. J. Bangladesh Agril. Univ. 13(1): 39-46, June 2015